Mixtures of persistent organic pollutants increase ovarian granulosa tumor cell line migration and spheroid invasion by upregulating MMP2 expression and activity via IGF1R. (30th March 2021) - Gogola-Mruk, Justyna; Hoffmann-Młodzianowska, Marta; Kamińska, Kinga; Ptak, Anna
Graphical abstract: Highlights: COV434 represent juvenile and KGN adult human ovarian granulosa tumor subtypes. In contrast to COV434 cells, KGN cells have migration and invasion potential. EDC mixtures stimulate KGN cells migration and spheroid invasion. EDC mixtures increase metalloproteinase 2 expression and activity in KGN cells. KGN spheroid invasion is induced by EDC mixtures through insulin-like growth factor 1 receptor. Abstract: Granulosa cell tumors (GCT) of the ovary have a good prognosis. Recurrence tends to be late; however, > 66 % of patients with recurrent GCT die from the disease. Most recurrences are abdominopelvic, although distant metastases have been documented. Here, we tested the hypothesis that a mixture of persistent endocrine-disrupting chemicals (EDCs) stimulates the invasion of GCT cells. We selected perfluorooctanoate (PFOA, 2 ng/mL), perfluorooctanesulfonate (PFOS, 8 ng/mL), 2, 2-dichlorodiphenyldichloroethylene ( p, p' -DDE, 1 ng/mL), polychlorinated biphenyl 153 (PCB153, 100 pg/mL), and hexachlorobenzene (HCB, 50 pg/mL), which have the highest measured concentrations in follicular fluid of women undergoing treatment with assisted reproductive technology. The human GCT cell lines COV434 and KGN have been used as in vitro models of juvenile (JGCT) and adult (AGCT) GCT subtypes, respectively. Cells were treated with a mixture of the test compounds for 15 min prior to analysis of protein phosphorylation; for 4 h prior to analysis in a circular chemorepellent-induced defect assay; for 6 h prior to analysis of matrix metalloproteinase 2 (MMP2) activity; for 24 h prior to analysis of migration, invasion, and gene expression; and for 48 h prior to analysis of protein expression. First, we showed that KGN cells migrated and exhibited invasive behavior. By contrast, COV434 cells lacked migration and invasion potential. Moreover, expression of mesenchymal genes and the gene encoding MMP2 was higher in KGN cells, and that of epithelial genes lower, than that in COV434 cells. Treatment of KGN cells with the EDC mixture stimulated cell migration, invasion, and lymphatic dissemination. The results suggest that the role of the EDC mixture in AGCT invasion is not related to changes in expression of epithelial and mesenchymal genes; rather, it is related to increased expression and activity of MMP2. Additionally, silencing insulin-like growth factor 1 (IGF1R) in AGCT abolished the stimulatory effect of the EDC mixture on KGN spheroid invasion. These results demonstrate that the EDC mixture increased KGN spheroid invasion by stimulating expression and activity of MMP2 via IGF1R.